Exercise adherence and wrist function recovery after distal radius fracture surgery in older adults: a 12 week prospective longitudinal study - Sunan Ji; Yiping Sun; Yu Zhu (Frontiers in Medicine, 2026)
Objective To explore the interactive relationship between wrist function recovery trajectory and exercise adherence in older patients after surgical treatment of distal radius fractures. Methods This study was a prospective, multicenter, observational study. A total of 230 older patients with distal radius fractures who underwent volar locking plate internal fixation at Nantong Sixth People's Hospital and Affiliated Hospital of Nantong University from February 2025 to February 2026 were enrolled. Wrist function was assessed using the Patient-Rated Wrist Evaluation (PRWE) at 2, 4, 8, and 12 weeks postoperatively. Exercise adherence was evaluated using the Orthopedic Patient Functional Exercise Adherence Scale. Wrist range of motion and grip strength were also measured. A linear mixed-effects model was used to analyze the functional recovery trajectory and the interaction effect between time and exercise adherence, with adjustment for potential confounders including age, sex, AO fracture classification, dominant hand injury, and baseline kinesiophobia level. Results The total PRWE score decreased from 68.5 ± 12.3 at 2 weeks postoperatively to 19.3 ± 9.7 at 12 weeks. The total exercise adherence score showed an initial increase followed by a decline, peaking at 4 weeks (61.8 ± 7.9). The linear mixed-effects model revealed significant main effects of time (β = −6.82, P < 0.001) and exercise adherence (β = −0.53, P < 0.001), as well as a significant interaction between time and adherence (β = −0.04, P = 0.043), indicating that patients with higher adherence exhibited faster functional recovery. Convergent validity analysis demonstrated moderate to strong correlations between PRWE and objective measures ( r = −0.39 to −0.71). Conclusion Exercise adherence was significantly associated with the functional recovery trajectory in older patients after distal radius fracture surgery, with higher adherence being related to a more favorable functional recovery trajectory. Clinically, attention should be paid to maintaining adherence during the 4- to 8-week postoperative period, and targeted interventions should be provided for patients with high levels of kinesiophobia.